2022
DOI: 10.3390/biomedicines10030647
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Ubiquitin-Proteasome System and Elevated Endoplasmic Reticulum Stress in Epilepsy

Abstract: The epilepsies are a broad group of conditions characterized by repeated seizures, and together are one of the most common neurological disorders. Additionally, epilepsy is comorbid with many neurological disorders, including lysosomal storage diseases, syndromic intellectual disability, and autism spectrum disorder. Despite the prevalence, treatments are still unsatisfactory: approximately 30% of epileptic patients do not adequately respond to existing therapeutics, which primarily target ion channels. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…Protein degradation can occur at both the intra- and extracellular levels via different mechanisms. Other recent works have already reviewed the role of intracellular systems including the ubiquitin−proteasome [ 46 ], autophagy−lysosome [ 47 ], and endosome–lysosome pathways [ 48 ] in physiological conditions and in neurological disorders, when they are altered. Similarly, extracellular degradation occurs via protease action and microglia or astrocyte phagocytosis, being significantly reduced in pathological conditions such as AD [ 49 ].…”
Section: Revising the Aβ Hypothesis And Dynamics—from The Anatomical−...mentioning
confidence: 99%
“…Protein degradation can occur at both the intra- and extracellular levels via different mechanisms. Other recent works have already reviewed the role of intracellular systems including the ubiquitin−proteasome [ 46 ], autophagy−lysosome [ 47 ], and endosome–lysosome pathways [ 48 ] in physiological conditions and in neurological disorders, when they are altered. Similarly, extracellular degradation occurs via protease action and microglia or astrocyte phagocytosis, being significantly reduced in pathological conditions such as AD [ 49 ].…”
Section: Revising the Aβ Hypothesis And Dynamics—from The Anatomical−...mentioning
confidence: 99%
“…One major disease-causing mechanism for the loss of function of GABA A receptors is that pathogenic variants lead to receptor trafficking deficiencies due to defective protein conformations 6,19 . Such epilepsy-associated GABA A receptor subunit variants cause protein misfolding and/or disrupt the subunit-subunit assembly process in the ER, resulting in a decrease in the surface expression of the pentameric receptors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical significance of these variants is not adequately addressed since most of them lack functional characterization and many of them are classified as uncertain or conflicting interpretations. For the limited number of characterized GABA A receptor variants, accumulating evidence indicated that proteostasis deficiency that resulted from misfolding and excessive degradation of the variants is a major disease-causing mechanism [13] . Adapting the ER proteostasis network pharmacologically corrected the misfolding and restored the surface trafficking and thus ion channel function for a variety of pathogenic GABA A receptor variants [14] .…”
Section: Introductionmentioning
confidence: 99%